Research progress on zeolite molecular sieve-based catalysts for VOCs catalytic combustion - JIANG Zhongyu; LIU Junchen; RUAN Hongcheng; JIA Yongsheng; DENG Wei; GUO Limin* (能源环境保护)
Volatile organic compounds (VOCs) are one of the major gaseous pollutants produced by industrial production, transport, and biomass combustion,which significantly affect atmospheric quality, ecological environment, and human health. With increased awareness of environmental protection and the implementation of air pollution control measures, the development of efficient VOCs treatment technology has become an urgent task. Catalytic combustion technology for VOCs, as an effective treatment method, has garnered significant attention due to its wide range of applications and high purification efficiency. Loaded catalysts, especially zeolite-based catalysts, exhibit promising prospects for industrial use by dispersing active components onto carriers, enabling efficient utilization and enhanced stability. This paper summarizes the research progress of zeolite-based catalysts for the catalytic combustion of VOCs from two perspectives: Regulating zeolite carriers and loading active components. Moreover, it discusses the effects of water vapor conditions and the presence of multi-component VOCs on the catalytic combustion of VOCs using zeolite-based catalysts. Finally, it presents an outlook on the current issues associated with zeolite-based catalysts. These research advances are expected to provide theoretical and practical references for environmental management and air quality improvement, while promoting the application and development of zeolite-based catalysts in VOCs management.